2016
DOI: 10.4103/2229-5151.177357
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus bolus tube feeds: Does the modality affect glycemic variability, tube feeding volume, caloric intake, or insulin utilization?

Abstract: Introduction:Enteral nutrition (EN) is very important to optimizing outcomes in critical illness. Debate exists regarding the best strategy for enteral tube feeding (TF), with concerns that bolus TF (BTF) may increase glycemic variability (GV) but result in fewer nutritional interruptions than continuous TF (CTF). This study examines if there is a difference in GV, insulin usage, TF volume, and caloric delivery among intensive care patients receiving BTF versus CTF. We hypothesize that there are no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Some studies have shown that continuous nasal feeding has advantages over intermittent nasal feeding and can effectively improve the quality of nursing. 18 20 In this study, evidence-based continuous nasal feeding practice was introduced into clinical practice, which can enable nurses to better understand evidence-based nursing and solidify nursing behavior in their daily work. This not only updated nurses’ knowledge of evidence-based continuous nasal feeding but also significantly improved their compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that continuous nasal feeding has advantages over intermittent nasal feeding and can effectively improve the quality of nursing. 18 20 In this study, evidence-based continuous nasal feeding practice was introduced into clinical practice, which can enable nurses to better understand evidence-based nursing and solidify nursing behavior in their daily work. This not only updated nurses’ knowledge of evidence-based continuous nasal feeding but also significantly improved their compliance.…”
Section: Discussionmentioning
confidence: 99%
“…I risultati hanno mostrato che l'alimentazione continua era stata più efficace sulla gestione e sulla stabilità della glicemia. Uno studio pilota prospettico randomizzato di Evans et al (2016) [11] effettuato su 50 soggetti in UTI chirurgica con PEG, hanno valutato l'impatto della NE sull'utilizzo dell'insulina e il tasso glicemico e concludono dicendo che non ci sono state differenze statistiche per età, sesso, punteggi APACHE II, punteggi di SAPS II, punteggi GCS, indice di massa corporea e intervalli di controllo dell'insulina nei due gruppi. Non ci sono state differenze statisticamente significative per quanto riguarda i risultati del: tempo medio del raggiungimento per l'obiettivo nutrizione ≥ 80%, interruzioni della NE e incidenza di ipoglicemia (≤75 mg/dl).…”
Section: Primo Gruppo: Modalità Bolo Vs Continuaunclassified
“…It also requires the subject to be attached to an infusion pump for significant periods of time. [ 1 ] Intermittent infusion mimics a more physiologic feeding process that allows greater subject mobility. Patients may also reach target enteral calories earlier [ 2 ] and decrease length of stay (LOS) and mortality.…”
Section: Introductionmentioning
confidence: 99%